Kith or Kin? Familiarity as a Cue to Kinship in Social Birds - Leedale, Amy E.; Li, Jianqiang; Hatchwell, Ben J. (Frontiers in Ecology and Evolution, 2020)
Interacting with relatives provides opportunities for fitness benefits via kin-selected cooperation, but also creates potential costs through kin competition and inbreeding. Therefore, a mechanism for the discrimination of kin from non-kin is likely to be critical for individuals of many social species to maximize their inclusive fitness. Evidence suggests that genetic cues to kinship are rare and that learned or environmental cues offer a more parsimonious explanation for kin recognition in most contexts. This is particularly true among cooperatively breeding birds, where recognition of familiar individuals is usually regarded as the most plausible mechanism for kin discrimination. In this article, we first review the evidence that familiarity provides an effective decision rule for discrimination of kin from non-kin in social birds. We then consider some of the complexities of familiarity as a cue to kinship, especially the problems of how individuals become familiar, and how familiar individuals are recognized. We conclude that while familiarity as a mechanism for kin recognition may be more parsimonious and widespread than genetic mechanisms, its apparent simplicity as a decision rule governing social interactions may be deceptive. Finally, we identify directions for future research on familiarity as a kin recognition mechanism in social birds and other taxa.